2019
DOI: 10.1186/s12883-019-1509-x
|View full text |Cite
|
Sign up to set email alerts
|

Low free triiodothyronineis predicts worsen neurological outcome of patients with acute ischemic stroke: a retrospective study with bioinformatics analysis

Abstract: BackgroudPatients with acute ischemic stroke (AIS) often experience low serum free triiodothyronine (FT3), but the association of low FT3 with stroke severity, subtype and prognosis has not yet been thoroughly studied, and the molecular events underlying these clinical observation were also unclear.MethodsWe retrospectively collected 221 cases of AIS and 182 non-AIS cases with detailed clinical data from our department. FT3 concentrations were measured on admission to predict functional outcome within 3 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 50 publications
(54 reference statements)
2
18
0
Order By: Relevance
“…Moreover, studies suggests that thyroid status may influence recovery, prognosis, and outcomes of rehabilitation in stroke patients, but published data provide partially inconsistent results [8][9][10][11][12]. Therefore, the complex interrelationships between the thyroid, the heart and the brain remain an area of interest with a potential for future prevention and treatment approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies suggests that thyroid status may influence recovery, prognosis, and outcomes of rehabilitation in stroke patients, but published data provide partially inconsistent results [8][9][10][11][12]. Therefore, the complex interrelationships between the thyroid, the heart and the brain remain an area of interest with a potential for future prevention and treatment approaches.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that FT3 levels were negatively correlated with IS incidence among young adults. This is the rst study to our knowledge to have reported such a relationship, as prior studies and meta-analysis have largely focused on correlations between low FT3 levels and severity/mortality among acute IS patients [23][24][25][26][27]. These prior studies have reported such a relationship even for low FT3 values within the standard reference range [28,29].…”
Section: Discussionmentioning
confidence: 74%
“…One study, however, found that this relationship was age-dependent, such that TT3 and FT3 levels were unrelated to IS outcomes in patients < 65 years old, whereas TT3 levels were independently predictive of poor outcomes among older patients [30]. In these prior studies, the average population ages ranged from 61.4-81.5 years [23][24][25][26][27][28], with the exception of one study with a median population age of 48 years [29]. Serum TT3 and FT3 levels are lower among healthy older individuals [31], and FT3 levels decline over time [32].…”
Section: Discussionmentioning
confidence: 99%
“…We also observed a shorter readmission-free period on low T3 patients, but no difference was detected in the length of stay or readmissions rate in the 6 month period. Other studies found a longer length of stay in patients in ICU ( 15 , 17 ). Besides, considering that the comparison is made with ICU patients, our finding suggests that low T3 levels could be seen as a marker of the severity of the disease as well as the metabolic alterations caused by it.…”
Section: Discussionmentioning
confidence: 83%
“…This pattern of thyroid hormone alterations was described in several scenarios of acute or chronic illness ( 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ). In addition, there is a significant correlation between altered thyroid hormone levels and the severity and duration of disease ( 9 , 10 , 11 , 12 , 17 , 18 , 19 , 20 ).…”
Section: Introductionmentioning
confidence: 80%